Uncover The Role of Brand Elements of Customer’s Choice for Sustainable Products - Krissanya, Nofriska; Berutu, Meta Bara; Febriatmoko, Bogy (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2025)
This research aims to determine the factors that can influence consumers' intention to purchase sustainable beauty and body care products. This study is centered on investigating the influence of various brand elements, including green brand positioning (GBP), brand perception (BP), green brand knowledge (GBK), and attitude toward green brand (AGB), on consumers' purchase intentions regarding these products. It is posited that brand elements play a pivotal role in enhancing the competitive dimension of a brand, particularly in the context of sustainable products. A quantitative method was employed in this research with 223 respondents in Indonesia. The Structural Equation Modeling (SEM) technique was used to analyze the data using Smart PLS 3.0. The results of the study indicate that all examined brand elements have a direct impact on consumers' attitudes, which ultimately influence consumers' intention to purchase sustainable beauty and body care products. Based on the findings of this research, companies can focus their strategies on brand elements such as positioning, perception, and knowledge to get high intention on sustainable beauty and body care products. Therefore, companies need to consider promotional messages that contain green values or empower communities that work on sustainable lifestyles to get more intention on this product.